Comparison of In-hospital Acute Inferior Wall Myocardial Infarction Outcomes in Elderly Patients with and without the Right Ventricular Involvement (Medical Forum Monthly, 2021)
Objective: The major aim of the current study is to determine the in-hospital outcomes of acute inferior wall myocardial infarction (IWMI) in elderly patients with the presence and absence of right ventricular myocardial infarction (RVMI).Study Design: A comparative cross-sectional studyPlace and Duration of Study: This study was conducted at the department of Cardiology in Ch. Pervaiz Elahi Institute of Cardiology Multan from March 2020 to March 2021 for a period of one-year.Materials and Methods: A cross-sectional study was designed using a sample size of 165 elderly patients with IWMI. The study was performed using a one-year patient’s data from Chaudhary Pervaiz Elahi Institute of Cardiology, Multan. Both male and female IWMI patients with age’s ≥60 years were considered for the study. Baseline data and risk factors were recorded for all patients after the informed consent. The older IWMI patients were categorized into two groups namely, the RVMI and non-RVMI groups respectively. In-hospital outcomes such as serious complications, cardiogenic shocks, complete AV blockage, ventricular tachycardia and in-hospital deaths were monitored.Results: Out of total 165 IWMI patients, 80 (48%) patients had RVMI whereas, the remaining 85 (52%) were non-RVMI patients. Our results show that RVMI is an important determinant of the in-hospital outcomes such as serious complications (76%), shock (48%), cardiogenic shocks (36%), complete AV blockage (38%) and in-hospital death rates (53%) in the elderly IWMI patients.Conclusion: Our study has shown that the RVI in older IWMI patients lead to frequent complications thus exacerbating and aggravating the in-hospital outcomes of acute IWMI due the increased risk of shocks, serious complications, cardiogenic shocks, complete AV blockage and in-hospital deaths.